Pengaruh Pelatihan dan Pengawasan terhadap Kinerja Pegawai pada Puskesmas Merlung Kabupaten Tanjung Jabung Barat - Nur Ema (Universitas Batanghari Jambi, 2021)
The analytical tool used in this research is quantitative descriptive analysis to measure the level of training and supervision of employee performance. To see the direction of the relationship between leadership style variables and work climate on job satisfaction using multiple regression. Using a statistical test to see how much influence training and supervision have on the performance of Merlung Health Center employees, Tanjung Jabung Barat Regency, using correlation and determinative coefficient analysis. Multiple linear regression using this study with the aim of entering the data studied into a regression equation model and proving the hypothesis regarding the alleged influence (training and supervision) as a means of independent variables on employee performance (as the dependent variable) simultaneously (together). ) or partially (own) by using software called the SPSS program. Based on the results of multiple regression analysis, the coefficients for the independent variables X1 = -0.344 and X2 = -0.330. Thus the regression equation model is written. The constant (a) is 4.770, the value of the employee performance variable is 4.770. The regression coefficient of the X1 training variable is -0.344, that training has a negative effect on employee performance. X2 supervision of -0.330 negative coefficient value indicates that a 1% decrease in supervision will reduce employee performance by 32.3%. Then it will be concluded that training and supervision have a significant effect on employee performance at the Merlung Health Center, Tanjung jabung Barat Regency. And the results obtained from a significant value smaller than 0.05, namely training 0.002 < 0.05 and supervision 0.000 < 0.05, it can be concluded that training and supervision have a significant influence on the performance of Merlung Public Health Center employees, Tanjung Jabung Barat Regency